Impact of Helicobacter pylori Infection and Outcome of Anti-Helicobacter pylori Therapy in Patients with Reflux Laryngopharyngitis. (5th July 2022) - Shen, Huili; Chen, Yijie; Li, Xiaohui; Yan, Jing; Zhao, Junjie; Kong, Demin; Shi, Yanxia; Li, Zhihui; Wang, Jihong; Shao, Na; Wang, Zhenghui
Abstract : Objectives . This study was designed to explore the relationship between Helicobacter pylori (Hp) infection and reflux laryngopharyngitis (RLP) and to evaluate the outcome of anti-Hp therapy in improving RLP symptoms. Methods . A total of 410 patients with RLP were enrolled and tested for Hp infection. The association of Hp infection with reflux symptom index (RSI) and reflux finding score (RFS) was determined. Hp-positive patients received either a proton pump inhibitor (PPI) omeprazole alone (control group) or a combination regimen (experimental group) consisting of omeprazole, mosapride citrate, amoxicillin, and clarithromycin. Therapeutic outcomes were compared 4 weeks later. Results . Of the 410 participants, 290 were Hp-positive and 120 Hp-negative. Both RSI and RFS were significantly higher in Hp-positive patients than in Hp-negative patients. Hp infection status was positively correlated with RSI (P < 0.05 ) and RFS (P < 0.05 ). The overall response rate was higher in the experimental group than in the control group. Both the groups had a significant reduction in RSI and RFS after therapy, with a greater improvement in the experimental group (P < 0.05 ). Conclusion . Our findings establish a link between Hp infection and RLP. Anti-Hp therapy improves RSI and RFS in RLP patients. Therefore, Hp eradication drugs may be added to the PPI-based regimen in the treatment of RLP.